Factorization is an art (6)

Algebra Level 4

{ ( x y + y z + z x ) 2 = 3 ( x 2 y 2 + y 2 z 2 + z 2 x 2 ) x + y + z = 2016 x y z = w 3 \large \begin{cases} (xy+yz+zx)^2 & = 3(x^{2}y^{2}+y^{2}z^{2}+z^{2}x^{2}) \\ x+y+z & = 2016 \\ xyz & = w^{3} \end{cases}

Let x , y , z x, y, z and w w be positive real numbers satisfying the system of equations above, enter your answer as the value of w w .


The answer is 672.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Ivan Koswara
Feb 17, 2017

By Cauchy-Schwarz inequality,

( ( x y ) 2 + ( x z ) 2 + ( y z ) 2 ) ( 1 2 + 1 2 + 1 2 ) ( x y 1 + x z 1 + y z 1 ) 2 ((xy)^2 + (xz)^2 + (yz)^2) \cdot (1^2 + 1^2 + 1^2) \ge (xy \cdot 1 + xz \cdot 1 + yz \cdot 1)^2

with equality if the vectors ( x y , x z , y z ) , ( 1 , 1 , 1 ) (xy, xz, yz), (1, 1, 1) are linearly dependent; in other words, x y = x z = y z xy = xz = yz , or x = y = z x = y = z . But we do achieve equality as given in the first equation. So x = y = z x = y = z . Plugging this to the second equation, we get x = y = z = 2016 3 = 672 x = y = z = \frac{2016}{3} = 672 , and plugging this to the third equation, we get w 3 = x y z = x 3 w^3 = xyz = x^3 , so w = x = 672 w = x = \boxed{672} (because w w is real, there's only one solution).

Tommy Li
Jul 11, 2016

( x y + y z + z x ) 2 = 3 ( x 2 y 2 + y 2 z 2 + z 2 x 2 ) (xy+yz+zx)^2 = 3(x^{2}y^{2}+y^{2}z^{2}+z^{2}x^{2})

x 2 y 2 + y 2 z 2 + z 2 x 2 + 2 x 2 y z + 2 x y 2 z + 2 x y z 2 = 3 ( x 2 y 2 + y 2 z 2 + z 2 x 2 ) x^{2}y^{2}+y^{2}z^{2}+z^{2}x^{2}+2x^2yz+2xy^2z+2xyz^2=3(x^{2}y^{2}+y^{2}z^{2}+z^{2}x^{2})

2 x 2 y 2 + 2 y 2 z 2 + 2 z 2 x 2 2 x 2 y z 2 x y 2 z 2 x y z 2 = 0 2x^{2}y^{2}+2y^{2}z^{2}+2z^{2}x^{2}-2x^2yz-2xy^2z-2xyz^2=0

( x 2 y 2 2 x 2 y z + z 2 x 2 ) + ( x 2 y 2 2 x y 2 z + y 2 z 2 ) + ( y 2 z 2 2 x y z 2 + z 2 x 2 ) = 0 (x^2y^2-2x^2yz+z^2x^2)+(x^2y^2-2xy^2z+y^2z^2)+(y^2z^2-2xyz^2+z^2x^2) =0

x 2 ( y 2 2 y z + z 2 ) + y 2 ( x 2 2 x z + z 2 ) + z 2 ( y 2 2 y x + x 2 ) = 0 x^2(y^2-2yz+z^2)+y^2(x^2-2xz+z^2)+z^2(y^2-2yx+x^2)=0

x 2 ( y z ) 2 + y 2 ( x z ) 2 + z 2 ( y x ) 2 = 0 x^2(y-z)^2+y^2(x-z)^2+z^2(y-x)^2=0

x 2 = y 2 = z 2 = 0 \Rightarrow x^2=y^2=z^2=0 (rej.)

y z = x z = y x = 0 \Rightarrow y-z=x-z=y-x=0

x = y = z \Rightarrow x=y=z

x + y + z = 2016 x+y+z = 2016

x = y = z = 672 \Rightarrow x=y=z=672

x y z = 67 2 3 xyz=672^{3}

w = 672 \Rightarrow w=672

Moderator note:

Before reading the comments, can you spot the error in the solution? If so, how could it be fixed?

In 7th step: How do you conclude that x 2 = y 2 = z 2 = 0 x^2=y^2=z^2=0 ?

A Former Brilliant Member - 4 years, 11 months ago

Log in to reply

That's a good point. That presents some issues.

Calvin Lin Staff - 4 years, 3 months ago

Because the LHS is written as the sum of 3 squared numbers and it equal to 0, so each square has to equal to 0. x 2 ( y z ) 2 = 0 x 2 = 0 or ( y z ) 2 = 0 x^2(y-z)^2=0\Rightarrow x^2=0\ \text{or}\ (y-z)^2=0

Hải Trung Lê - 4 years, 10 months ago

Unfortunately, the conclusion from x 2 ( y z ) 2 + y 2 ( x z ) 2 + z 2 ( y x ) 2 = 0 x^2(y-z)^2+y^2(x-z)^2+z^2(y-x)^2=0 is not that x 2 = y 2 = z 2 = 0 x^2 = y^2 = z^2 = 0 or ( y x ) = ( x z ) = ( y x ) = 0 (y-x) = (x-z) = ( y-x) = 0 .

Instead, it is just x ( y z ) = y ( x z ) = z ( y x ) = 0 x(y-z) = y(x-z) = z (y-x) = 0 . There are then 8 possibilities to consider, and not just 2. Eg. we could have x = 0 , x z = 0 , z = 0 x = 0, x - z = 0, z = 0 and y y is anything!

Calvin Lin Staff - 4 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...